Synthesis and Anti-Tumour Activity Evaluation of Bergenin Derivatives. (October 2015) - Yang, Yanxia; Yan, Jianwei; Yan, Fulin; Yin, Yanyan; Zhuang, Fangfang
A series of triazole derivatives of bergenin were synthesised through the nucleophilic substitution reaction of bergenin and propargyl bromide, and following click reaction with different azides. Their antitumour activities were evaluated against EC9706, MGC803 and B16 in vitro. Several compounds showed potent anti-tumour activity, especially (2S, 3R, 4R, 4aS, 10bR)-8, 10-bis1-[4-(tert-butyl)benzyl]-1H-1, 2, 3-triazol-4-yl methoxy-3, 4-dihydroxy-2-(hydroxymethyl)-9-methoxy-2, 3, 4, 4a-tetrahydropyrano[3, 2-c]isochromen-6(10bH)-one, with IC50 value down to 6.28 μmol L -1 against EC970.